Hubungan Tingkat Kecemasan dengan Lama Kala I di Bidan Praktek Mandiri Belakang Pondok Kota Bengkulu - Safitri, Riska; Ratiyun, Rafidaini Sazarni; Pawiliyah, Pawiliyah (Nursing Inside Community, 2019)
Anxiety is a normal condition that may be felt by every woman in dealing with labor process, but this condition causes psychiatric problems that inhibit labor process. The aims of this study was to determine relationship between level of anxiety with prolonged stage I on labor mother at Midwife Practice Bengkulu City. The design of this study was cross sectional study. Population in this study were all primigravida mothers with prolonged stage I of who labored at Midwife Practice Bengkulu City with the amount of 30 people. The data analysis technique was performed by the Exact Fisher?s test. The results of this study showed there is a relationship between level of anxiety with prolonged stage I on labor mother primigravida at Midwife Practice Bengkulu City (p = 0.001 <0.05) with a close relationship category. It is expected that primigravida labor mothers will further increase the desire to find out about information so that with good knowledge will reduce the level of anxiety during labor process.